Synthesis of acetylated glucose esters of palm fatty acids and their properties as surfactants - Obaje, Olobo Jonathan (2000)
The present esterification methods for producing sugar-based fatty esters are faced with the problems of low yields, the use of toxic solvents and thermal instabilities of sugars. This project reviewed and modified a number of esterification methods with the view to overcome these problems. The methods studied include direct heating, acid anhydride, enzymatic, and chemical transesterification and interesterification methods. Subsequently, a solvent-free, low temperature chemical interesterification method, yielding up to 90% product (mainly mono- and di-fatty acid substituted acetylated glucopyranoses) was developed. The method involved the heating of glucose pentaacetate (GPA), with appropriate fatty acid methyl ester (FAME) in the presence of Na-metal catalyst, under reduced pressure. The optimal reaction conditions were found to be 1:3 mole ratio of GPA and FAME, respectively; 0.5% Na-metal catalyst; reaction temperatures of 85 - 90°C; reaction time of 5 to 6 hrs, and at 20 mmHg pressure. Six acetylated glucose fatty esters (AGFE) were obtained as products using FAME of palm (PO) and palm kernel (PKO) fatty acids, C6 to CIO (C6110) mixed fatty acids, and oleic and stearic fatty acids. The reactions leading to the fonnation of the mono- and di-substituted acetylated glucose fatty esters were found to follow zero-order kinetics. Results from fatty-acyl group selectivity studies show that the longer-chain fatty acyl groups were generally preferred to the shorter chain-lengths. A novel nuclear magnetic resonance (NMR) spectroscopic method for determining the molecular structures of polyacetylated glucose fatty esters was developed in the course of this work. Using heteronuclear multiple bond correlation (HMBC) technique and the fatty acyl substituent-induced changes (SCS) in the BC-chemical shifts of the carbonyl-carbon atoms, the molecular structures of the mono- and disubstituted products were established as I-O-fatty acyl 2,3,4,6-acetyl a-Dglucopyranose and 1, 6-0-fatty acyI2,3,4-acetyl a-D-glucopyranose, respectively. The surface activity properties of the products were studied. AGFE was not soluble in water due to the lack of free -OH groups in the molecular structure, thus limiting the hydrophilic character of the pyranosyl head groups. Hydrophile-lipophile balance (HLB) experiments showed that AGFE from stearic acid and PKO were potential water-in-oil (W/O) emulsifiers while AGFE from PKO, PO and oleic acid showed moderate oil-in-water (O/W) emulsion stabilization. Cytotoxic experiments involving cancerous (HT -29 colon carcinoma and CEM-SS, T-cell lymphoblastic leukemia) and normal (3T3 normal mouse fibroblast) cell lines have shown that AGFE were non-cytotoxic towards cancer and normal cell lines The results of the antimicrobial experiments showed that the di-subsituted PNO product (PKO-2) to have a moderate activity against P. aeruginosa with inhibition zone diameter of 14.0mm and weakly active against S. auerus, B. subtilis 828 and 829. AGFE from PKO (PKO-l) was weakly active against P. aeruginosa with inhibition zone diameter of9.0mm. These compounds can thus perform the dual role as emulsifiers and preservatives.